2010
DOI: 10.1104/pp.110.154278
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing around 5-Hydroxyconiferyl Alcohol-Derived Units in Caffeic Acid O-Methyltransferase-Deficient Poplar Lignins  

Abstract: Caffeic acid O-methyltransferase (COMT) is a bifunctional enzyme that methylates the 5-and 3-hydroxyl positions on the aromatic ring of monolignol precursors, with a preference for 5-hydroxyconiferaldehyde, on the way to producing sinapyl alcohol. Lignins in COMT-deficient plants contain benzodioxane substructures due to the incorporation of 5-hydroxyconiferyl alcohol (5-OH-CA), as a monomer, into the lignin polymer. The derivatization followed by reductive cleavage method can be used to detect and determine b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 27 publications
4
39
0
1
Order By: Relevance
“…The observation of benzodioxane substructure in COMT down-regulated switchgrass was consistent with previous reports that down-regulation of COMT during lignin biosynthesis resulted in the incorporation of 5-hydroxy coniferyl alcohol into lignin and generation of novel benzodioxane units Vanholme et al, 2010). For example, Lu et al (2010) reported that down-regulation of COMT in poplar led to the formation of benzodioxane units in lignin. Similarly, Vanholme et al (2010) observed the newly formed benzodioxane units in COMT down-regulated Arabidopsis.…”
Section: Hsqc Nmr Analysissupporting
confidence: 79%
See 2 more Smart Citations
“…The observation of benzodioxane substructure in COMT down-regulated switchgrass was consistent with previous reports that down-regulation of COMT during lignin biosynthesis resulted in the incorporation of 5-hydroxy coniferyl alcohol into lignin and generation of novel benzodioxane units Vanholme et al, 2010). For example, Lu et al (2010) reported that down-regulation of COMT in poplar led to the formation of benzodioxane units in lignin. Similarly, Vanholme et al (2010) observed the newly formed benzodioxane units in COMT down-regulated Arabidopsis.…”
Section: Hsqc Nmr Analysissupporting
confidence: 79%
“…For instance, COMT down-regulation of lignin in poplar has resulted in a decrease in lignin content, formation of benzodioxane, and a substantial decrease in syringyl units (Jouanin et al, 2000;Lu et al, 2010).…”
Section: Lignin Related Recalcitrance Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ther esulting 5-hydroxyguaiacyl units react by typical 4-O-b-coupling with any of the hydroxycinnamyl alcohol monomers (the prototypical monolignols or further 5-hydroxyconiferyl alcohol), but the internal trapping of the intermediate quinone methide product by the novel 5-OH results in the formation of benzodioxane structures in the polymer. [11,92,[135][136][137][138][139] Benzodioxane levels can be amplified through acombination of F5H upregulation and COMT downregulation. In Arabidopsis,t he resulting plants may incorporate up to ca.…”
Section: Entry Speciesmentioning
confidence: 99%
“…1.3A), Arabidopsis, aspen (Populus tremuloides), corn, perennial ryegrass, poplar (Populus tremula x alba), silver birch, Stylosanthes humilis, switchgrass, tall fescue and tobacco, COMT down-regulation causes a large reduction in S units, leading to lower S/G ratio and highlighting the involvement of COMT in S lignin biosynthesis. COMT down-regulation is usually accompanied by the appearance of 5-hydroxyguaiacyl units in lignin due to incorporation of 5-hydroxy-coniferyl alcohol with unique benzodioxane structures (Jouanin et al, 2000;Ralph et al, 2001aRalph et al, , 2001bMarita et al, 2003a;Morreel et al, 2004;Lu et al, 2010). An increase in biphenyl (5-5) and phenylcoumaran (β-5) lignin linkages has also been detected in COMT-deficient plants.…”
Section: Caffeic Acid O-methyltransferasementioning
confidence: 99%